Housing markets, liquidity constraints and labor mobility - Markus Haavio; Heikki Kauppi (Bank of Finland, 2000)
Recent European data indicate that countries where a large proportion of the population lives in owner-occupied housing are experiencing higher unemployment rates than countries where the majority of people live in private rental housing, which might suggest that rental housing enhances labor mobility.In this paper, we develop a simple intertemporal two-region model that allows us to compare owner-occupied housing markets to rental markets and to analyze how these alternative arrangements allocate people in space and time.Consistent with the empirical observations, we find that the interregional labor market is more fluid under rental housing than under owner-occupation.As a result of greater mobility, the rental arrangement also results in better allocational efficiency than owner-occupation.When dwellings are rented, the decision to move to a booming region is largely based on current productivity, whereas under owner-occupation random wealth effects encourage deviations from this optimal behavior.
URN:NBN:fi:bof-20140807350
Keywords: 330